STUDENTS’ PERCEPTIONS TOWARDS E-QUIZZES IN ONLINE EFL CLASSROOMS - Huong, Luu Thi (VNU Journal of Foreign Studies; Vol 38 No 6DO - 10.25073/2525-2445/vnufs.4886, 2022)
Technology is being increasingly integrated into teaching environments in view of enhancing EFL students’ online learning experience. This article presents the outcomes of research employing a motivation theory technique to examine students’ experience using game-play quizzes at a university in Vietnam. Questionnaires and focus group interviews with students were used to learn about the extent to which students perceive e-quizzes in their learning process. Quantitative data collected was analyzed using SPSS and Huberman’s (1994) analytical framework was used to clarify qualitative data from interviews. Key findings based on quantitative data revealed that almost all students presented favourable views towards quizzes use. Findings from the interview noted that online quizzes enriched the quality of student learning in the classroom, with the highest influence reported on motivation, enjoyment and improved preparation and participation. The study also suggests that the use of online games in the classroom is likely to raise competitiveness, thereby improving intellectual stimulation, long-term retention of knowledge and digital skills.